Partisipasi Masyarakat Dalam Pembangunan Sumber Daya Manusia Kelurahan Semolowaru Kecamatan Sukolilo Kota Surabaya - Ertien Rining Nawangsari; Thoyib Hadiriyanto; Aldy Argarida Ichsan Nur Putra (Jurnal Penelitian Administrasi Publik, 2020)
In making development equitable, the Government of Indonesia issued a policy called regional autonomy. This regional autonomy is Law Number 32 of 2004 which has the function to regulate and manage governmental affairs in the surrounding area. So this regional autonomy aims to accelerate economic growth and regional development. At present there are still many developments that are still less profitable for the community, due to the lack of socialization in the implementation of development. In the absence of participation from the surrounding community, the implementation of development is not necessarily going well, because if the community does not provide participation such as proposals to the government about what is needed for life and daily life, then the government will also not know the implementation of development that is really needed by Public. As well as the factors that are driving the obstacles to the implementation of community participation. This research aims to find out the extent of the community participation in Semolowaru village in developing human resources. The method used in this research is descriptive qualitative method, the data collection technique is carried out using the literature review approach from several previous journals that can be used as a reference or reference in conducting research. The results of this study indicate that community participation in the development of human resources in Semolowaru Urban Village, Sukolilo Sub-district, Surabaya City, has resulted in a good implementation of development. With the proposals from the community and willingness to participate as well as the principle of mutual cooperation and heterogeneous living, making Semolowaru village in 2011-2012 was once one of the best kelurahans. And has a record of winning quite a lot of rewards. Keywords: Participation, Community, Development